TRANSDERMAL NITROGLYCERIN FOR THE TREATMENT OF PRETERM LABOR: A SYSTEMATIC REVIEW AND META-ANALYSIS - CONDE-AGUDELO, Agustín (2013)
OBJECTIVE: To evaluate the efficacy and safety of transdermal nitroglycerin as tocolytic agent in women with preterm labor. STUDY DESIGN: Systematic review and meta-analysis of randomized controlled trials. RESULTS: Thirteen studies (1302 women) were included. Two studies evaluated transdermal nitroglycerin versus placebo (N=186), 9 evaluated transdermal nitroglycerin versus β(2)-adrenergic-receptor agonists (N=1024), and 1 each evaluated transdermal nitroglycerin versus nifedipine (N=50) and transdermal nitroglycerin versus magnesium sulfate (N=42). There were no significant differences between transdermal nitroglycerin and placebo for delivery within 48 hours of initiation of treatment or before 28, 34 or 37 weeks’ gestation, adverse neonatal outcomes, and neurodevelopmental status at 24 months of age. Nevertheless, one study found a marginally significant reduction in the risk of a composite outcome of significant neonatal morbidity and perinatal mortality (3/74 [4.1%] versus 11/79 [13.9%]; relative risk 0.29, 95% confidence interval 0.08–1.00). When compared with β(2)-adrenergic-receptor agonists, transdermal nitroglycerin was associated with a significant reduction in the risk of preterm birth <34 and <37 weeks’ gestation, admission to the neonatal intensive care unit, use of mechanical ventilation, and maternal side effects. There were no significant differences between transdermal nitroglycerin and nifedipine and magnesium sulfate in delivery within 48 hours of treatment and pregnancy prolongation, respectively. Overall, women receiving transdermal nitroglycerin had a higher risk of headache. CONCLUSION: Although transdermal nitroglycerin appears to be more effective than β (2)-adrenergic-receptor agonists, the current evidence does not support its routine use as tocolytic agent for the treatment of preterm labor. Further additional double-blind placebo-controlled trials are needed.